ChemInform Abstract: Substituent Effect of Bis(pyridines)iodonium Complexes as Iodinating Reagents: Control of the Iodocyclization/Oxidation Process. Issue 34 (1st August 2013) - Okitsu, Takashi; Yumitate, Saki; Sato, Kana; In, Yasuko; Wada, Akimori
Abstract Preliminary investigations with the racemic substrate (I) reveal that, depending on the complex used, either a 2, 3‐dihydropyrrole or a pyrrole structure is formed.